Blood Bank Connect: Streamlining Blood Donation Processes Through a Mobile Application - Solihan, Muhammad Zulfahme; Mat Rejab, Mazidah (Applied Information Technology And Computer Science, 2025)
The growing demand for efficient blood donation systems exposes the limitations of traditional approaches, which suffer by communication breakdowns and manual processes. The goal of this research is to create Blood Bank Connect, a mobile application that will help donors, blood bank administrators, and healthcare providers coordinate donations, manage inventory, and communicate more effectively. Using an Waterfall methodology, the system offers automated notifications, and inventory management. The findings show considerable increases in donor involvement and inventory accuracy, illustrating the power of digital solutions in addressing systemic inefficiencies. Future study should look into scaling the platform for greater use and implementing advanced analytics for predictive demand forecasting.